KAJIAN STRATEGIS PENGEMBANGAN POTENSI EKOWISATA DI LEMBAH BALIEM SEBAGAI SUATU ALTERNATIF PENGELOLAAN PARIWISATA BERKELANJUTAN - ASSO, BONI; ADNYANA MANUABA, IB; SUNARTA, I NYOMAN (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
An alternative that could contribute positively to the conservation of the environment is the development of ecotourism based on consistency in adopting its principles. As an initial step in the development of attractive ecotourism object, ideally an inventory should be made first in order to avoid mistakes that could happen. Lembah Baliem area is so rich in potential ecotourism resources which, however, have not yet been managed on the basis of the concept of ecotourism approach. Based on such background this research accommodates the potential available in Lembah Baliem area in order to learn the possibility of developing sustainable ecotourism there. The objective of this research is to know the potential for developing ecotourism, to learn the obstacles to be faced, and to set the strategy for the development of ecotourism resources to be adopted for Lembah Baliem. This research is conducted in Lembah Baliem area, which administratively belongs to the regency of Jayawijaya, Papua Province. The data used in this research include both qualitative and quantitative data in accordance with the need of the research. The data also include both the primary and secondary data. The sampling in this research is based on nontest data collecting instrument, in which the data is obtained through interview, questionnaire, observation, and documentation. Finally, the data already collected is categorized, discussed and analyzed using the SWOT matrix under SHIP approach. The research identification result shows that Lembah Baliem area has fairly varied and natural ecotourism resources, such as: 8 caves, 8 location of festival shows, 3 historical monuments, 3 biggest likes, 4 mummies, 4 beautyfull panarome site, The obstacles of Baliem Ecotourism development are distance, stakeholder participation, knowledge of ecotourism concept still limited and the index of tourist visiting still low. Tourism development in Lembah Baliem still concerned to mass tourism management strategy. According the result could be concluded that the ecotourism potential to be developed, bud the development blocked by accessibility and human resources, so it should be solve out by 11 strategic solution. The handling of those obstacle need stakeholder involving base of sustainable ecotourism development, then give priority for straight access to West Papua.
Keywords: Strategic analysis, ecotourism, sustainable development.